Proposal for Growth and Development Evaluation Chart of Physical Abilities in Preschool Children-Analysis based on wavelet interpolation model- - Fujii, Katsunori; Tanaka, Nozomi; Ishigaki, Tohru; Sakai, Toshiro; Hayakawa, Kentaro (European Journal of Applied Sciences, 2022)
Growth and development evaluations of physical abilities (physique, motor ability) in preschool children are generally done with uniform evaluation charts of evaluation ranges based on cross-sectional data. In recent years, objective evaluation methods with least squares approximation polynomials have also been established. However, variability cannot be ruled out when using cross-sectional data on the growth and development of physical abilities in preschool children, and so physical development evaluations based on longitudinal changes with age, taking date of birth into account, have not been established. Of course, there are times when methods for constructing evaluations cannot be established. In this study, we applied the wavelet interpolation model to physical ability measurements corresponding to year and month of age, in order to evaluate growth and development of physical abilities associated with longitudinal aging over three years in boys 3 to 5 years old in Japan. First, standard age-related changes were investigated. Physical growth fundamentally tends to occur gradually, but body weight increases with slight fluctuations. In standard development of motor ability, particularly in the 20-m dash, fluctuating trends were seen near 3 years old, but there was a converging tendency in fluctuations associated with aging. In the tennis ball throw, the biological variation was pronounced, and there were large individual differences. Based on these trends, the effectiveness of applying the wavelet interpolation model became clear in this study. Hence, we applied the wavelet interpolation model to the mean values and standard deviations for the growth and development of physical abilities associated with aging over a span of three years during early childhood, and constructed an age span evaluation chart. With this evaluation chart, an evaluation that can correspond flexibly to growth and development in physical ability could be said to have been constructed.